2021
DOI: 10.1111/liv.14904
|View full text |Cite
|
Sign up to set email alerts
|

The crosstalk network of XIST/miR‐424‐5p/OGT mediates RAF1 glycosylation and participates in the progression of liver cancer

Abstract: Background Liver cancer is a major public health concern, but the mechanistic actions of biomarkers contributing to liver cancer remain to be determined. In this study, we aimed to investigate the regulatory cascade of microRNA‐424‐5p (miR‐424‐5p), X‐inactive‐specific transcript (XIST) and O‐GlcNAc transferase (OGT) in liver cancer. Methods Differentially expressed miRNAs and target genes related to liver cancer were predicted by bioinformatics analyses, and their expression was determined in liver tissues of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Our results showed that XIST played essential roles in regulating cell migration and invasion, as silencing by siRNA significantly inhibited these functions in multiple HNC cells. These carcinogenic roles were also confirmed in previous cancer studies, such as liver ( 50 ), ovarian ( 51 ), and esophageal cancer ( 52 ). A review by Zhou et al.…”
Section: Discussionsupporting
confidence: 83%
“…Our results showed that XIST played essential roles in regulating cell migration and invasion, as silencing by siRNA significantly inhibited these functions in multiple HNC cells. These carcinogenic roles were also confirmed in previous cancer studies, such as liver ( 50 ), ovarian ( 51 ), and esophageal cancer ( 52 ). A review by Zhou et al.…”
Section: Discussionsupporting
confidence: 83%
“…Hsa-mir-125b-5p was also found to be downregulated in bladder ( Canturk et al, 2014 ) and prostate cancer ( Lin et al, 2020 ). XIST, a lncRNA, has been shown to promote the progression of various cancers through its high expression ( Liu et al, 2018b ; Liu et al, 2019 ; Ning et al, 2021 ; Zheng et al, 2021 ). We found that the upregulated lncRNA XIST targets both hsa-mir-124-3p and hsa-miR-125b-5p and is positively correlated with CDKN2A.…”
Section: Discussionmentioning
confidence: 99%
“…A more detailed mechanism of XIST is demonstrated in hepatocellular carcinoma, in which inhibiting XIST expression contributes to overexpression of miR-424-5p. This miRNA degrades OGT and suppresses RAF1 glycosylation, resulting in favorable normal features in HCC cell lines [ 28 ].…”
Section: Cancer Cell Linesmentioning
confidence: 99%